2021
DOI: 10.1371/journal.pone.0261055
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Awareness, and Practices (KAP) towards COVID-19 among the marine fishers of Maharashtra State of India: An online cross-sectional Analysis

Abstract: The knowledge, awareness, and practices (KAP) about COVID-19 among the marine fishers who are engaged in the high-risk occupations and depend on the vulnerable sources of income in the Maharashtra state of India, were investigated to understand the behavioral changes and vulnerability among the respondents because of COVID-19. Data were collected through an online survey from 1st July to 30th July 2020 during the first peak of COVID-19 in the study area by using the questionnaire. Authors based on the latest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(56 reference statements)
1
5
0
Order By: Relevance
“…We examined how information related to the pandemic was accessed. The findings revealed, similar to previously reported studies, that the most used sources to access COVID-19 related information included national TV and social networks (17,40). In support of previous research (41) social media platforms, particularly Facebook and WhatsApp were also found to be popular sources, particularly among younger populations, those who reside alone alongside those in paid employment and those with higher education status.…”
Section: Discussionsupporting
confidence: 89%
“…We examined how information related to the pandemic was accessed. The findings revealed, similar to previously reported studies, that the most used sources to access COVID-19 related information included national TV and social networks (17,40). In support of previous research (41) social media platforms, particularly Facebook and WhatsApp were also found to be popular sources, particularly among younger populations, those who reside alone alongside those in paid employment and those with higher education status.…”
Section: Discussionsupporting
confidence: 89%
“…Despite the fact that the Fishers were not privileged as other areas, they were well informed of the COVID-19 diseases, its symptoms and precautions because unconcerned attitude of people leads to spread of the disease (Zhong et al2017). Supporting Wasave et al (2021) findings, Liu et al (2022) reported that better educated Fishers with higher income had more knowledge of COVID-19 in Fuqing, China. On the contrary, Fishers in Kashmir Valley though illiterates, were well informed of COVID-19 and so they acted accordingly to reduce spread of the disease (Siddique et al 2022).And in fishing communities in Bangladesh, the crisis reduced demand for fish that brought about a fall in the price of fish negatively affecting Fishers livelihood ( Hoque et al 2021).…”
Section: Theoretical Reviewmentioning
confidence: 72%
“…Knowledge gained through authorities from scientific findings such as COVID-19 pandemic spreads fast to all areas including fishing communities. According to Wasave et al (2021), age and education contribute highly to the knowledge, attitude and practice of Fishers of Maharashtra State of India. Despite the fact that the Fishers were not privileged as other areas, they were well informed of the COVID-19 diseases, its symptoms and precautions because unconcerned attitude of people leads to spread of the disease (Zhong et al2017).…”
Section: Theoretical Reviewmentioning
confidence: 99%
“…Although studies exploring awareness [12][13][14][15][16][17][18][19][20][21][22][23], health-seeking behavior [24][25][26], and stigma related to COVID-19 [27,28] have been reported from different parts of India, to the best of our knowledge, this is the first community-based study to have been conducted in the northeast region (NER) of India, which has distinct cultural beliefs and practices. Moreover, the previously reported studies were either conducted online [12-20, 23, 25-28] or telephonically [21,24], or within specific population subgroups [13,17,20,22,[24][25][26][27][28], which may result in biased inferences due to lack of generalizability [29,30]. A comprehensive understanding of the community perception and health-seeking behavior can enable policy makers to plan mitigation and control measures to effectively tackle future pandemics.…”
Section: Introductionmentioning
confidence: 99%